The Galician Language in the Portuguese Teatro de Cordel: Linguistic Study - Carrasco González, Juan M. (Madrygal. Revista de Estudios Gallegos, 2020)
The Portuguese teatro de cordel of the eighteenth century includes some pieces with the character of the galician. It’s about a burlesque portrait of the galician inmigrants that moved to Portugal in large numbers, especially to the city of Lisbon. In this paper the analysis of their language is carried out, which is a Portuguese with features of the Galician language and dotted with castillianisms of diverse kind.
Keywords: Galician Language; History of Language; Teatro de Cordel; Portuguese Literature